A Note on the Horizontal–Vertical Illusion – A Reply to Wade (2014). (June 2016) - Landwehr, Klaus
Like many others before him, Nicholas Wade, in a recent publication in this journal, did not provide the correct title of Adolf Fick's dissertation, approved by the University at Marburg, Germany, in 1851, and Wade also wrongly attributed now famous illusion figures, meant to illustrate the so-called horizontal-vertical illusion (the +, the L, and the inverted T), to this author. After having corrected these errors, I briefly relate Fick's work to modern work in the field and note that it has been widely neglected.